Glycolytic flux control by drugging phosphoglycolate phosphatase - Jeanclos, Elisabeth; Schlötzer, Jan; Hadamek, Kerstin; Yuan-Chen, Natalia; AlWahsh, Mohammad; Hollmann, Robert; Fratz, Stefanie; Yesilyurt-Gerhards, Dilan; Frankenbach, Tina; Engelmann, Daria; Keller, Angelika; Kaestner, Alexandra; et al. (Nature Communications, 2022)
Targeting the intrinsic metabolism of immune or tumor cells is a therapeutic strategy in autoimmunity, chronic inflammation or cancer. Metabolite repair enzymes may represent an alternative target class for selective metabolic inhibition, but pharmacological tools to test this concept are needed. Here, we demonstrate that phosphoglycolate phosphatase (PGP), a prototypical metabolite repair enzyme in glycolysis, is a pharmacologically actionable target. Using a combination of small molecule screening, protein crystallography, molecular dynamics simulations and NMR metabolomics, we discover and analyze a compound (CP1) that inhibits PGP with high selectivity and submicromolar potency. CP1 locks the phosphatase in a catalytically inactive conformation, dampens glycolytic flux, and phenocopies effects of cellular PGP-deficiency. This study provides key insights into effective and precise PGP targeting, at the same time validating an allosteric approach to control glycolysis that could advance discoveries of innovative therapeutic candidates.